Innovation, the public and the third space: understanding the role of boundary objects in open laboratory work - Hu, Mengwei; Fritzsche, Albrecht (Technology Analysis & Strategic Management, 2021)
We study how the design of work environments in open laboratories affects the engagement of visitors in innovation processes. For this purpose, we present evidence from an embedded case study of five innovation projects in an open laboratory in Central Europe. Theoretically, we build on the concept of boundary objects and investigate which types of boundaries are addressed by the design of the different work environments. We identify three interaction schemes in which boundaries are addressed very differently. We find that open laboratories as spaces for interaction between different organisations and communities can give account of multiple perspectives on innovation and diverging attributions of meaning, if appliances and equipment in the labs allow for the emergence of appropriate boundary objects.
Created from Fastlane, Scopus look-up
Keywords: Boundary objects; participatory design; third space; user innovation